Feasibility of video‐based skill assessment for percutaneous nephrostomy training in Senegal - Rebecca Hisey; Fatou Bintou Ndiaye; Kyle Sunderland; Idrissa Seck; Moustapha Mbaye; Mohammed Keita; Mamadou Diahame; Ron Kikinis; Babacar Diao; Gabor Fichtinger; Mamadou Camara (Healthcare Technology Letters)
Abstract Percutaneous nephrostomy can be an effective means of preventing irreparable renal damage from obstructive renal disease thereby providing patients with more time to access treatment to remove the source of the blockage. In sub‐Saharan Africa, where there is limited access to treatments such as dialysis and transplantation, a nephrostomy can be life‐saving. Training this procedure in simulation can allow trainees to develop their technical skills without risking patient safety, but still requires an ex‐pert observer to provide performative feedback. In this study, the feasibility of using video as an accessible method to assess skill in simulated percutaneous nephrostomy is evaluated. Six novice urology residents and six expert urologists from Ouakam Military Hospital in Dakar, Senegal performed 4 nephrostomies each using the setup. Motion‐based metrics were computed for each trial from the predicted bounding boxes of a trained object detection network, and these metrics were compared between novices and experts. The authors were able to measure significant differences in both ultrasound and needle handling between novice and expert participants. Additionally, performance changes could be measured within each group over multiple trials. Conclusions: Video‐based skill assessment is a feasible and accessible option for providing trainees with quantitative performance feedback in sub‐Saharan Africa.